Spinal Inhibition of GABAB Receptors by the Extracellular Matrix Protein Fibulin-2 in Neuropathic Rats - Papon, Marie-Amélie; Le Feuvre, Yves; Barreda-Gómez, Gabriel; Favereaux, Alexandre; Farrugia, Fanny; Bouali-Benazzouz, Rabia; Nagy, Frédéric; Rodríguez-Puertas, Rafael; Landry, Marc (Frontiers in Cellular Neuroscience, 2020)
In the central nervous system, the inhibitory GABAB receptor is the archetype of heterodimeric G protein-coupled receptors (GPCRs). Receptor interaction with partner proteins has emerged as a novel mechanism to alter GPCR signaling in pathophysiological conditions. We propose here that GABAB activity is inhibited through the specific binding of fibulin-2, an extracellular matrix protein, to the B1a subunit in a rat model of neuropathic pain. We demonstrate that fibulin-2 hampers GABAB activation, presumably through decreasing agonist-induced conformational changes. Fibulin-2 regulates the GABAB-mediated presynaptic inhibition of neurotransmitter release and weakens the GABAB-mediated inhibitory effect in neuronal cell culture. In the dorsal spinal cord of neuropathic rats, fibulin-2 is overexpressed and colocalized with B1a. Fibulin-2 may thus interact with presynaptic GABAB receptors, including those on nociceptive afferents. By applying anti-fibulin-2 siRNA in vivo, we enhanced the antinociceptive effect of intrathecal baclofen in neuropathic rats, thus demonstrating that fibulin-2 limits the action of GABAB agonists in vivo. Taken together, our data provide an example of an endogenous regulation of GABAB receptor by extracellular matrix proteins and demonstrate its functional impact on pathophysiological processes of pain sensitization.